Optimal design of a flying-wing aircraft inner wing structure configuration - Huang, Haidong (Cranfield University, 2012)
Flying-wing aircraft are considered to have great advantages and potentials in aerodynamic performance and weight saving. However, they also have many challenges in design. One of the biggest challenges is the structural design of the inner wing (fuselage). Unlike the conventional fuselage of a tube configuration, the flying-wing aircraft inner wing cross section is limited to a noncircular shape, which is not structurally efficient to resist the internal pressure load. In order to solve this problem, a number of configurations have been proposed by other designers such as Multi Bubble Fuselage (MBF), Vaulted Ribbed Shell (VLRS), Flat Ribbed Shell (FRS), Vaulted Shell Honeycomb Core (VLHC), Flat Sandwich Shell Honeycomb Core (FLHC), Y Braced Box Fuselage and the modified fuselage designed with Y brace replaced by vaulted shell configurations. However all these configurations still inevitably have structural weight penalty compared with optimal tube fuselage layout. This current study intends to focus on finding an optimal configuration with minimum structural weight penalty for a flying-wing concept in a preliminary design stage. A new possible inner wing configuration, in terms of aerodynamic shape and structural layout, was proposed by the author, and it might be referred as ‘Wave-Section Configuration’. The methodologies of how to obtain a structurally efficient curvature of the shape, as well as how to conduct the initial sizing were incorporated. A theoretical analysis of load transmission indicated that the Wave-Section Configuration is feasible, and this was further proved as being practical by FE analysis. Moreover, initial FE analysis and comparison of the Wave-Section Configuration with two other typical configurations, Multi Bubble Fuselage and Conventional Wing, suggested that the Wave-Section Configuration is an optimal design in terms of weight saving. However, due to limitations of the author’s research area, influences on aerodynamic performances have not yet been taken into account.
Keywords: Flying-wing aircraft; inner wing configuration; Wave-Section Configuration; optimal; FE analysis